CLINICAL IMMUNOLOGIC GROUNDS FOR LOCAL INTERFERON USE IN ACUTE VIRAL INFECTION TREATMENT - I.N. Zakharova; V.V. Malinovskaya; N.A. Korovina; Kh.I. Kurbanova; N.S. Glukhareva; N.V. Koroid ("Paediatrician" Publishers LLC, 2011)
Broad spectrum of antiviral activity of interferons lays grounds to its use in complex therapy of acute viral infections. It has been shown that antiviral and antibacterial interferon activity reveals itself while used both systematically and locally. Clinical efficacy of locally applied viferon is accompanied by nasal mucosa cytokine status changes, as has been shown in nasal swabs. There has been shown dependency of local immune response on the age, severity of the disease, clinical forms of respiratory syndrome, bacterial complications, if present, intensity and characteristics of viral contamination against the background of viferon treatment. Key words: acute respiratory viral disease, interferon, cell immunity, humoral immunity, interferon status, cytokine status, recombinant α-interferon, immunocorrection. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (5): 117-123.)